Analytical methods for studies and experiments on "Transforming the force" - Davis, Paul K., 1943-; Bigelow, James H.; McEver, Jimmie; Rand Corporation; National Defense Research Institute (U.S.) (Santa Monica, CA : RAND, 1999)
The Department of Defense is motivated by both opportunities and necessity to "transform the force" over the years ahead by exploiting modern technology and operational concepts associated with the revolution in military affairs, and by making related organizational changes. This documented briefing provides a background review describing a broad transformation strategy, then discusses and illustrates how analysis supported by models and simulations (including gaming) can supplement and guide empirical work such as joint experiments. The approach is illustrated for the problem of halting an invading army, with long-range precision fires playing a major role. A great deal of insight about the general problem can be obtained from analysis at different levels of resolution with a family of models. This process, in turn, identifies important kinds of information that can be obtained only from empirical work such as joint field experiments. The recommended experiments are then quite different from those that would probably be accomplished without the benefit of prior analysis. Failure to approach warfare research with such a model-test-model approach can squander rare opportunities for field experiments and lead to serious misinterpretations of limited experimental events.
"National Defense Research Institute."
Includes bibliographical references (p. 57-59).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: National security -- United States -- Planning -- Methodology; Strategy; United States -- Armed Forces -- Reorganization -- Planning; United States -- Defense; United States -- Military policy -- Planning -- Methodology